2021
DOI: 10.1038/s41598-021-82117-3
|View full text |Cite
|
Sign up to set email alerts
|

Minor allele of GJA1 gene polymorphism is associated with higher heart rate during atrial fibrillation

Abstract: Atrial fibrillation (AF) tachycardia causes heart failure and requires more attention. The genetic background of individual heart rate (HR) variations during AF are unclear. We hypothesized that HR-associated single nucleotide polymorphisms (SNPs) reported in Genome-Wide Association Studies (GWAS) are also associated with HR during AF. We enrolled patients with persistent AF (311 for screening and 146 for replication) who underwent AF ablation and were genotyped for the 21 h-associated SNPs reported in GWAS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Our group showed that the GJA1 SNP rs1015451 (T > C) minor allele, which encodes the connexin-43, was significantly associated with higher AF heart rate. 48 However, this SNV is not consistent with AF-related SNVs and is one of the heart rate-related SNVs during sinus rhythm. 49 Zeemering et al, who performed RNA sequencing in the right and left atrial appendage tissue of AF patients, detected genes associated with persistent but could not find a gene associated with heart failure.…”
Section: Clinical Features and Af-associated Snvsmentioning
confidence: 83%
See 2 more Smart Citations
“…Our group showed that the GJA1 SNP rs1015451 (T > C) minor allele, which encodes the connexin-43, was significantly associated with higher AF heart rate. 48 However, this SNV is not consistent with AF-related SNVs and is one of the heart rate-related SNVs during sinus rhythm. 49 Zeemering et al, who performed RNA sequencing in the right and left atrial appendage tissue of AF patients, detected genes associated with persistent but could not find a gene associated with heart failure.…”
Section: Clinical Features and Af-associated Snvsmentioning
confidence: 83%
“…Our group showed that the GJA1 SNP rs1015451 (T > C) minor allele, which encodes the connexin‐43, was significantly associated with higher AF heart rate. 48 However, this SNV is not consistent with AF‐related SNVs and is one of the heart rate‐related SNVs during sinus rhythm. 49 …”
Section: History Of Genetic Analysis Of Afmentioning
confidence: 86%
See 1 more Smart Citation
“…Hsu et al [ 34 ] reported that subjects with AF carrying the ALDH2*2 polymorphism showed more severe oxidative stress in their atria compared with non-carriers and suggested that ALDH2 may protect from AF-related remodeling. In a single-center retrospective study, Okamura and colleagues [ 36 ] analyzed the SNPs reported in a GWAS analysis of patients with persistent AF and demonstrated that the GJA1 SNP rs1015451 has increased the risk for a higher heart rate during AF. Furthermore, Liu et al [ 37 ] reported that the ACE2 SNP rs4646188 was related to a larger left atrial end-systolic diameter and associated with a higher AF risk among Uygur patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress in genome-wide association (GWAS) analysis in recent years, genomics has made considerable progress in the prediction of complex human diseases, such as CAD and AF [32]. To date, over 50 pathogenic gene mutations have been revealed to cause AF, which mainly involve cellular signal molecules [33], myocardial structural proteins [34], ion [35] and gap junction channels [36]. Hsu et al [34] reported that subjects with AF carrying the ALDH2*2 polymorphism showed more severe oxidative stress in their atria compared with non-carriers and suggested that ALDH2 may protect from AF-related OR in adjusted model was adjusted for LAD, LVDd, LVSd, LVEF, ALT, AST, UN, Scr, UA, CAD, HF, use of ACEIs, BBs, MRAs, digoxin and diuretics OR: odds ratio; CI: confidence interval.…”
Section: Discussionmentioning
confidence: 99%